Effect of carperitide on the 1 year prognosis of patients with acute decompensated heart failure. (4th February 2022) - Nogi, Kazutaka; Ueda, Tomoya; Matsue, Yuya; Nogi, Maki; Ishihara, Satomi; Nakada, Yasuki; Kawakami, Rika; Kagiyama, Nobuyuki; Kitai, Takeshi; Oishi, Shogo; Akiyama, Eiichi; Suzuki, Satoshi; et al.
Abstract: Aims: Acute heart failure (AHF) is a clinical syndrome with a poor prognosis and a major public health concern worldwide. The aim of this study was to investigate whether carperitide administration improves the 1 year prognosis of patients with AHF and to check whether there is an optimal dose of the drug. Methods and results: We analysed the data of COOPERATE‐HF‐J (the Consortium for Pooled Data Analysis regarding Hospitalized Patients with Heart Failure in Japan), combining two cohorts (NARA‐HF and REALITY‐AHF), which included 2435 patients with acute decompensated heart failure. The patients were divided into no carperitide (NO‐ANP, n = 1098); very low‐dose carperitide (VLD‐ANP, <0.02 μg/kg/min, n = 593); and low‐dose carperitide groups (LD‐ANP, ≥0.02 μg/kg/min, n = 744). The primary endpoint was cardiovascular mortality within 1 year after admission. The secondary endpoints were all‐cause mortality and rehospitalization due to worsening heart failure within 1 year after admission. The median carperitide doses in the VLD‐ANP and LD‐ANP groups were 0.013 and 0.025 μg/kg/min, respectively. Kaplan–Meier analysis showed that cardiovascular mortality and all‐cause mortality were significantly lower in the LD‐ANP group than in the NO‐ANP and VLD‐ANP groups ( P < 0.001 and P = 0.002, respectively). Multivariable Cox regression analysis for cardiovascular and all‐cause mortality revealed that LD‐ANP was significantly associated with lower cardiovascular and all‐cause mortality within 1 year after admission, even after adjusting other covariates (hazard ratio: 0.696 and 0.791, 95% confidence interval: 0.513–0.944 and 0.628–0.997, P = 0.020 and 0.047, respectively). Conclusions: Low‐dose carperitide was significantly associated with lower cardiovascular and all‐cause mortality within 1 year after admission. Our results suggest the necessity for well‐designed randomized controlled trials to determine the doses of carperitide that could improve clinical outcomes in patients with AHF.